Movimentos sociais, mercado e internet: o ativismo gordo no Brasil - Lourenço, Bruna Scanavachi (2022)
This study details the diffusion of critical ideas about fatness present in Fat Activism and Fat Studies in three main spaces: academic world, internet and markets. In order to understand how the narrative that fights fatphobia circulates through these spaces, the concepts of social space, everyday activism, and the process of incorporating the critique of social movements in the capitalist system are articulated in the academic field of critical studies of fat, in the social movement that fights fatphobia on the internet and in the collective narrative about fat in market spheres. Based on the premises of Economic Sociology, the mapping of the international context of the field of critical fat studies contextualizes Brazilian studies and identifies activism as part of the Fat Studies habitus; Brazilian activism on the social network Instagram shows itself as a type of everyday activism that targets culture and employs individualized actions that claim a fat identity as a form of resistance to the discriminatory narratives of fat; and finally, the relationship between companies and activists identifies the process of appropriation of activist discourses by capitalism as the gateway to the movement against fatphobia in the concept of organizational diversity, a dynamic that contributes to the legitimization of fatphobia as discrimination and shows progress in the transformation of the collective narrative of fat sought by the Fat Activism social movement and by Fat Studies. The context of critical fat studies was chosen given the emergence of addressing the gap between scientific evidence and misconceptions in the collective narrative about fat that supports weight stigma, narrative inconsistent with modern scientific knowledge that is just as harmful as racial and gender discrimination. This research offers contributions to the social movement when it highlights the social structure and the game that takes place between society and the narratives of fat, as well as for the critical academic space on fat, given the nascent stage of the Brazilian space that needs research interdisciplinary approaches that bring it closer to the international context and to the field of organizational research by highlighting the dynamics of appropriation of criticism by companies and its relationship with the concept of organizational diversity.